Descriptive Study of Child Identification and Assessment Implementation Dyslexia in Bandung - Maulana, Arif Fakhrudin (Jurnal Asesmen Dan Intervensi Anak Berkebutuhan Khusus, 2024)
Identification and assessment are important activities for early detection of children with special needs. Assessments are carried out to determine conditions and characteristics, abilities, obstacles, and strengths, as well as needs. This research aims to describe the implementation of identification and assessment, identify the obstacles experienced in implementing identification and assessment of dyslexia students, and explain the solutions in implementing identification and assessment of dyslexia students. This research uses a descriptive method with a qualitative approach, with data collected. Through interviews, observation, and documentation. Based on the research results, the implementation of identification and assessment of dyslexia students at the X Intervention Lab in Bandung is not optimal. Barriers to the implementation of identification and assessment of dyslexia students include understanding dyslexia, the process of identifying and assessing dyslexia, parental support, and collaboration with educational experts and professional staff. Solutions applied in the implementation of identification and assessment of dyslexia students include studying and understanding dyslexia as well as carrying out identification and assessment, collaborating with students' parents, dealing with dyslexia students directly by researchers without having to refer them to experts, and preparing creative media to help dyslexia students read.